María Elena Placencia y Xose A. Padilla (eds.). Guía práctica de pragmática del español. Londres-Nueva York: Routledge, 2020, ISBN: 978-0-8153-5772-8. 280 páginas. (Estudios Humanísticos. Filología, 2021)
Reseña